Modulation algorithms of power electronic converters for shaping of conducted interference - Loschi, Hermes (2023)
Remarkably, over the last few decades, the electromagnetic interference within 9 to 150 kHz was especially accentuated since the switching frequency of power electronic converters is still limited to several kHz. Thus, bringing up the debate on regulation. From the point of view of the electromagnetic interference noise shape, two cases represent the extremes of possibilities among the various possible converter control algorithms: the deterministic and pseudo-random modulation.